2023
DOI: 10.3389/fmicb.2023.1254060
|View full text |Cite
|
Sign up to set email alerts
|

Molecular typing of canine parvovirus type 2 by VP2 gene sequencing and restriction fragment length polymorphism in affected dogs from Egypt

Asmaa Magouz,
Ismail El-Kon,
Enrique Raya-Álvarez
et al.

Abstract: IntroductionCanine parvovirus-2 (CPV-2) is one of the most common infectious diseases in dogs characterized by severe gastroenteritis, vomiting, and bloody diarrhea. Little information is available about this topic in Egypt, particularly in the Delta region. This study reports the prevalence and molecular analysis of CPV-2 variants collected from El-Gharbia and Kafrelsheikh governorates in the Delta of Egypt.MethodsIn this study, 320 rectal swabs were collected from infected domestic dogs from two districts in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 35 publications
(49 reference statements)
0
0
0
Order By: Relevance
“…Mekky et al [ 22 ] in Egypt and Ngwa et al [ 32 ] in Cameroon were unclear as to why CPV-2 infections were significantly more prevalent among German shepherd and Pit Bull breeds than in other breeds. Other studies carried out in Egypt reported that Pit Bull [ 33 ], German Shepherd [ 34 ], and Rottweiler [ 22 ] breeds were significantly associated with a higher risk of CPV-2 infections than other breeds of dogs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mekky et al [ 22 ] in Egypt and Ngwa et al [ 32 ] in Cameroon were unclear as to why CPV-2 infections were significantly more prevalent among German shepherd and Pit Bull breeds than in other breeds. Other studies carried out in Egypt reported that Pit Bull [ 33 ], German Shepherd [ 34 ], and Rottweiler [ 22 ] breeds were significantly associated with a higher risk of CPV-2 infections than other breeds of dogs.…”
Section: Discussionmentioning
confidence: 99%
“…Abdel-Rhman et al [ 42 ], Awad et al [ 43 ], Al-hosary et al [ 21 ], and Etman et al [ 44 ] reported that CPV-2a and CPV-2b are the predominant viruses isolated from infected dogs in Egypt. Zaher et al [ 18 ] and Elbaz et al [ 20 ] previously recorded the CPV-2c genotype in Egypt, while Magouz et al [ 34 ] in a neighboring governorate to the study area indicated that only CPV-2a and CPV-2c were circulating in that area. These latter studies were carried out in restricted geographic regions and time periods, and only partial fragments of the VP2 gene were analyzed.…”
Section: Discussionmentioning
confidence: 99%